2019
DOI: 10.1371/journal.pone.0221022
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non-communicable diseases among HIV positive patients on antiretroviral therapy at joint clinical research centre, Lubowa, Uganda

Abstract: Introduction Antiretroviral therapy (ART) has changed the course of HIV/AIDs by enabling patients to live longer, raising concern of the co- existence of HIV with other chronic illnesses, notably non-communicable diseases (NCDs). NCDs are on the rise in developing countries and evidence shows higher occurrence among people living with HIV (PLHIV). In Uganda, the burden of NCDs among PLHIV remains largely unquantified. Objective To determine the prevalence of hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 11 publications
7
28
2
Order By: Relevance
“…As people got older they became more prone to different NCDs like hypertension and geriatric diabetes. This was consistent with several studies done in several LMICs where older participants in the cohorts were more likely to be diagnosed with NCDs [15][16][17][18][19][20].…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…As people got older they became more prone to different NCDs like hypertension and geriatric diabetes. This was consistent with several studies done in several LMICs where older participants in the cohorts were more likely to be diagnosed with NCDs [15][16][17][18][19][20].…”
Section: Plos Onesupporting
confidence: 92%
“…It is thus imperative to examine the effect of the burden of NCDs on PLHIV in LMICs, focusing on NCDs such as diabetes mellitus, hypertension, cancers, and obesity. Kansiime et al found a 20.7% chance of developing at least one NCD in PLHIV in Uganda, whilst the most prevalent NCD was found to be hypertension [18]. The high prevalence of NCD risk factors and unrecognized and untreated hypertension represent major problems [19].…”
Section: Introductionmentioning
confidence: 99%
“…systematic reviews outside SSA suggest that sexual minorities exhibit higher rates of NCDs [11]. Contrastingly, study findings from SSA point to comparably lower prevalence rates of NCDs (4.7%, 11.5% and 21.2%) among general population PLHIV clients [5,13,23,24].…”
Section: Plos Onementioning
confidence: 78%
“…COVID-19 poses a particular challenge for the African continent because of existing high prevalence rates of other infectious diseases including human immunodeficiency virus (HIV)/ acquired immunodeficiency syndrome (AIDS), TB, cholera, and malaria, along with high rates of AMR and a disproportionate burden of poverty ( UNAIDS, 2019 ; World Health Organisation, 2019 ; WHO, 2019a ; Ataguba, 2020 ; Godman et al., 2020a ; Simpson, 2020 ; United Nations Economic Commission for Africa, 2020a ; WHO, 2020b ; WHO, 2020c ), with ongoing infectious disease initiatives appreciably challenged by COVID-19 ( Mendelson and Matsoso, 2015 ; Ghana Ministry of Health, 2018 ; Godman et al., 2020a ; Kowalska et al., 2020 ). The presence of multi-morbidity with NCDs will aggravate the situation further ( Oni et al., 2015 ; So-Armah and Freiberg, 2018 ; Achwoka et al., 2019 ; Chang et al., 2019 ; Kansiime et al., 2019 ; Woldesemayat, 2020 ), with already high rates of CVD and diabetes a growing concern across Africa ( Mensah et al., 2015 ; Godman et al., 2020b ; Godman et al., 2020c ).…”
Section: Introductionmentioning
confidence: 99%